URGENSI PENGATURAN KEADILAN RESTORATIF (RESTORATIVE JUSTICE) SEBAGAI DASAR PENGHENTIAN PENANGANAN TINDAK PIDANA - Dewa Nugraha, Achmad (UNES Journal of Swara Justisia, 2023)
Restorative justice is currently often used by law enforcement institutions in resolving criminal cases that are being handled. However, there is no regulation that explicitly regulates so that there is one common view of each law enforcement institution in implementing restorative justice so that it is not uncommon to find a criminal offense being stopped based on restorative justice but for other institutions involved in the criminal justice system in Indonesia the case cannot be stopped with a restorative justice approach. This research aims to provide an overview of the implementation of restorative justice as a basis for terminating the handling of criminal cases and how the implementation of restorative justice will be in the future in the termination of criminal cases. the method used in this journal is a normative research method based on regulations and other legal sources relevant to this journal. In this journal, it can be understood that currently there are still different views from each law enforcement institution on criminal offenses that can be resolved with restorative justice, with these different views it is time for Indonesia to have a special regulation related to restorative justice which is a common reference for each law enforcement institution in implementing restorative justice and in this journal the author provides input regarding the types of criminal offenses that can be stopped handling based on restorative justice.